Gut hormone secretion, gastric emptying, and glycemic responses to erythritol and xylitol in lean and obese subjects - Wölnerhanssen, Bettina K.; Cajacob, Lucian; Keller, Nino; Doody, Alison; Rehfeld, Jens F.; Drewe, Juergen; Peterli, Ralph; Beglinger, Christoph; Meyer-Gerspach, Anne Christin (American journal of physiology: endocrinology and metabolism, 2016)
With the increasing prevalence of obesity and a possible association with increasing sucrose consumption, nonnutritive sweeteners are gaining popularity. Given that some studies indicate that artificial sweeteners might have adverse effects, alternative solutions are sought. Xylitol and erythritol have been known for a long time and their beneficial effects on caries prevention and potential health benefits in diabetic patients have been demonstrated in several studies. Glucagon-like peptide-1 (GLP-1) and cholecystokinin (CCK) are released from the gut in response to food intake, promote satiation, reduce gastric emptying (GE), and modulate glucose homeostasis. Although glucose ingestion stimulates sweet taste receptors in the gut and leads to incretin and gastrointestinal hormone release, the effects of xylitol and erythritol have not been well studied. Ten lean and 10 obese volunteers were given 75 g of glucose, 50 g of xylitol, or 75 g of erythritol in 300 ml of water or placebo (water) by a nasogastric tube. We examined plasma glucose, insulin, active GLP-1, CCK, and GE with a [ 13 C]sodium acetate breath test and assessed subjective feelings of satiation. Xylitol and erythritol led to a marked increase in CCK and GLP-1, whereas insulin and plasma glucose were not (erythritol) or only slightly (xylitol) affected. Both xylitol and erythritol induced a significant retardation in GE. Subjective feelings of appetite were not significantly different after carbohydrate intake compared with placebo. In conclusion, acute ingestion of erythritol and xylitol stimulates gut hormone release and slows down gastric emptying, whereas there is no or only little effect on insulin release.